Medical attention of animals in the Hispanic kingdoms during the Late Middle Ages - Ferragud, Carmel (Medievalism, 2011)
During the Middle Ages many animals received medical care (horses, farm animals, migratory flocks, animals of zoological collections). Most of these attentions were carried out within the domestic framework and by the same people who were in charge, thanks to their empirical knowledge handed down from generation to generation orally, but sometimes also written. Only for the care of some animals to high price came a group of dedicated individuals with much greater intensity, and sometimes making this their craft, especially to take care of their health (marshal, hawkers...).